2004
DOI: 10.4314/ajtcam.v2i1.31099
|View full text |Cite
|
Sign up to set email alerts
|

Gossypol content on leaves and seeds from some wild <i>Malvaceae</i> species

Abstract: Ten Malvaceae species were analysed for their seed and leaf gossypol content by HPLC.The results showed that gossypol is common in most of the Malvaceae family, but its concentration varies among the species and also among the varieties of the same specie. We found that Hampea integerrina Schldt., had two fold more gossypol in its seeds than Gossypium hirsutum L., from which the compound was initially isolated and its antifertility effect studied. The toxic effects of gossypol earlier observed against several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…1978) have also been identified in several Mesoamerican Malvoideae. For instance, high amounts of gossypol were detected in seeds from species of Anoda and Hibiscus (Sotelo et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1978) have also been identified in several Mesoamerican Malvoideae. For instance, high amounts of gossypol were detected in seeds from species of Anoda and Hibiscus (Sotelo et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, digestive inhibitors, such as gossypol (Meisner et al 1978) have also been identified in several Mesoamerican Malvoideae. For instance, high amounts of gossypol were detected in seeds from species of Anoda and Hibiscus (Sotelo et al 2005). Circumventing digestive inhibitors in legumes may represent -for a given bruchid lineage -a pre-adaptation to overcome the action of other secondary compounds such as gossypol, and make possible a further radiation on Malvaceae.…”
Section: Host-plant Associationmentioning
confidence: 99%
“…[11][12][13][14] It has also been found in a few other genera belonging to Gossypioideae. [15][16][17][18] Due to hindered rotation about the pivot bond between the two naphthyl moieties, axial dissymmetry of the molecule gives rise to the existence of (-)-and (+)-enantiomers, with the absolute configuration R and S, corresponding to the helical sense M and P, respectively. 19,20 While being a toxic contaminant of cottonseed products, gossypol exhibits a number of potentially useful biological activities, including cytotoxic activity.…”
mentioning
confidence: 99%
“…Some segments of GP permits on to the soapstock as natural a form or as an intricate with related constituents of the oil like phosphatides (Dowd, 1996;Kuk and Ballew, 1993). Numerous researchers mentioned antioxidant activity of GP attained from raw cotton oil (Mukhamediev et al, 1986;Cai et al, 2004;Sotelo et al, 2005;Wang et al, 2005;Boboev et al, 2012). As it is well defined that peroxide value (PV) is a measure of peroxides and hydro peroxides concentration formed in the initial stages of lipid oxidation.…”
Section: Anticancer Activity Of Cottonseed Oilmentioning
confidence: 99%